Effects of inter-element spacing and number of elements on planar array antenna characteristics - Adnan, Noor Hidayah Muhamad; Islam, Md Rafiqul; Alam, A H M Zahirul (Institute of Advanced Engineering and Science (IAES), 2018)
Planar array antenna is seen as one of the innovative solutions of massive MIMO and 5G networks since they provide directive beams. In this paper, planar array antenna with square and rectangular arrangements based on 2 x 2 antenna elements as one subarray was proposed. Then, array factor for the the planar array antenna with up to 64 antenna elements was calculated to analyze the effects of inter-element spacing and number of elements on the antenna characteristics. Higher values of inter-element spacing contributed to higher number of side lobes, narrower main lobe, higher directivity and lower half power beamwidth (HPBW). Inter-element spacing equals to 0.5λ was found to be the most suitable value for planar array antenna design based on the analysis. Meanwhile, higher number of antenna elements increased the value of directivity of the planar array with narrower HPBW. Therefore, there is a tradeoff between directivity and HPBW in designing planar array antenna for massive MIMO application.